2015
DOI: 10.1093/mnras/stv2594
|View full text |Cite
|
Sign up to set email alerts
|

Modelling CH3OH masers: Sobolev approximation and accelerated lambda iteration method

Abstract: A simple one-dimensional model of CH 3 OH maser is considered. Two techniques are used for the calculation of molecule level populations: the accelerated lambda iteration (ALI) method and the large velocity gradient (LVG), or Sobolev, approximation. The LVG approximation gives accurate results provided that the characteristic dimensions of the medium are larger than 5-10 lengths of the resonance region. We presume that this condition can be satisfied only for the largest observed maser spot distributions. Fact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…where k C is the absorption coefficient of the dust at the line frequency, k L φ(x) is the line opacity coefficient, φ(x) = exp(−x 2 )/π 1/2 , x = (ν −ν lm )/∆ν lm . The details of the calculations of the loss probability function see in Nesterenok (2016).…”
Section: B2 System Of Master Equations For Level Population Densitiementioning
confidence: 99%
“…where k C is the absorption coefficient of the dust at the line frequency, k L φ(x) is the line opacity coefficient, φ(x) = exp(−x 2 )/π 1/2 , x = (ν −ν lm )/∆ν lm . The details of the calculations of the loss probability function see in Nesterenok (2016).…”
Section: B2 System Of Master Equations For Level Population Densitiementioning
confidence: 99%
“…The maser emission of typical size of ∼1000 au Sarniak et al 2018) can arise in outer parts of the circumstellar disc, in the interface between the disc and envelope or in outflows (Sanna et al 2010(Sanna et al , 2017Goddi et al 2011;Moscadelli et al 2011). Theoretical prediction of radiative pumping by mid-infrared photons from dust grains (Cragg et al 2005;Nesterenok 2016) appears to be strongly supported by recent observations of synchronized flares of the maser and infrared emissions in two HMYSOs Hunter et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, ad hoc selection rules were adopted to reproduce inversion population in these transitions (e.g., Johnston et al 1992 andCragg et al 1992). Recent models (McEwen et al 2014;Nesterenok 2016) have confirmed that CIMMs mase in different density ranges.…”
mentioning
confidence: 84%